Lean thinking applied to logistics : a case study - Michkov, Vladislav (2022)
The following work demonstrates the application of lean in a logistics company, answering the following question: “How can lean improve the logistics company’s processes?”. To answer the introduced question, a literature review was conducted, a documental analysis, direct observation and semi-structured and unstructured interviews were carried out. After that being completed, different lean recommendations were suggested to reduce or even eliminate wastes in the company. Some of the tools suggested were poka-yoke, cellular layout, kaizen and visual management. It wasn’t possible to verify the efficiency of the suggested tools since the investigation was done during the pandemic scenario, which enabled the author to spend more time in the company and due to the short time of the internship. As a future investigation, it is proposed to consider all the suggestions proposed, hire at least one lean specialist to explain to the employees what is lean and why it is so beneficial, and to switch to a digital workplace environment like Microsoft 365.